IMF Staff Papers, Volume 55, No. 4. (IMF Staff Papers; IMF Staff Papers ;, 2008)
In this issue, John T. Cuddington and Daniel Jerrett from the Colorado School of Mines examine whether metals prices are in a "super cycle" upswing driven by intensive economic growth in China, in particular. Using evidence from U.S. Social Security records, James E. Duggan, Robert Gillingham, and John S. Greenlees look at the empirical relationship between mortality and lifetime income. Par Osterholm and Jeromin Zettelmeyer analyze the effect of external conditions on growth in Latin America, while Junko Koeda presents a debt overhang model for low-income countries. The issue also includes a comprehensive index for Volume 55 (2008) by author, subject, and title.